POSITION OF HAKAMAIN IN DIVORCE ON THE REASON OF SYIQAQ ACCORDING TO LAW NUMBER 50 OF 2009 AMENDMENT OF LAW NUMBER 3 OF 2006 AMENDMENT OF LAW NUMBER 7 OF 1989 - Rokhim, Abdul (Awang Long Law Review, 2021)
The purpose of the marriage is in fact, not a few couples who experience shocks - shocks in building their household, which can eventually find failure in their marriage. Failure to build a household usually ends in divorce. Although the families of both parties have tried to reconcile and improve the couple so that the couple does not experience divorce. One of the reasons for the divorce is due to the couple having quarrels and disputes constantly so that it can not be reconciled. The quarrel between the husband and wife may be due to Nusyuz’s wife (disobedient) or it may also be due to the husband behaving badly towards his wife so that the husband and wife can no longer be reconciled. This is as confirmed in the Compilation of Islamic Law in article 116 letter (f) Jo PP No. 19 of 1975 in the Letter (f) that is the occurrence of continuous quarrels, This continuous quarrel in Islamic law is called "syiqaq". Especially in the case of syiqaq in accordance with the provisions of Article 76 paragraph (2) of Law Number 7 of 1989 Amendment to Law Number 3 of 2006 Second Amendment of Law-Law Number 50 of 2009, then the panel of judges may appoint each judge from the family the plaintiff as well as the defendant’s family. The jury was asked to be more sensitive to whether there were any indications that the plaintiff and defendant could be reconciled with the presence of the family. From the examination it is intended to be clear to the jury about the reasons for the dispute and quarrel, where the judge makes an intervening decision and sends to each of the plaintiffs and defendants to return with the family at a time determined by the jury.